Effects of dietary live or heat‐inactivated autochthonous Bacillus pumilus SE5 on growth performance, immune responses and immune gene expression in grouper Epinephelus coioides. (23rd March 2015) - Yan, Y.‐Y.; Xia, H.‐Q.; Yang, H.‐L.; Hoseinifar, S.H.; Sun, Y.‐Z.
Abstract: To evaluate the possible dietary application of live and heat‐inactivated probiotic Bacillus pumilus SE5 in grouper Epinephelus coioides, juveniles (14.6 ± 0.2 g) were fed either a basal control diet (without probiotic) or the basal diet supplemented with 1.0 × 10 8 CFU g −1 live (T1) and heat‐inactivated B. pumilus SE5 (T2). The heat‐inactivated probiotic significantly improved the final weight, weight gain (WG) and specific growth rate (SGR) at day 60 and significantly decreased the feed conversion ratio (FCR) at day 30 and 60, while the viable probiotic significantly decreased the FCR at day 60 ( P < 0.05). Phagocytic activity, serum complement C3 and IgM levels as well as SOD activity elevated significantly in fish fed the heat‐inactivated probiotic for 60 days ( P < 0.05). Furthermore, the heat‐inactivated probiotic remarkably up‐regulated expression of TLR2 and pro‐inflammatory cytokines (IL‐8 and IL‐1β) in head kidney ( P < 0.05), but the viable probiotic failed to do so. These results indicated that heat‐inactivated B. pumilus SE5 can effectively improve the growth performance and immune responses of E. coioides .